Decavanadate effects in biological systems - Aureliano, M. (2012)
Vanadium biological studies often disregarded the formation of decameric vanadate species known to interact, in vitro, with high-affinity with many proteins such as myosin and sarcoplasmic reticulum calcium pump and also to inhibit these biochemical systems involved in energy transduction. Moreover, very few in vivo animal studies involving vanadium consider the contribution of decavanadate to vanadium biological effects. Recently, it has been shown that an acute exposure to decavanadate but not to other vanadate oligomers induced oxidative stress and a different fate in vanadium intracellular accumulation. Several markers of oxidative stress analyzed on hepatic and cardiac tissue were monitored after in vivo effect of an acute exposure (12, 24 h and 7 days), to a sub-lethal concentration (5 mM; 1 mg/kg) of two vanadium solutions (‘‘metavanadate’’ and ‘‘decavanadate’’). It was observed that ‘‘decavanadate’’ promote different effects than other vanadate oligomers in catalase activity, glutathione content, lipid peroxidation, mitochondrial superoxide anion production and vanadium accumulation, whereas both solutions seem to equally depress reactive oxygen species (ROS) production as well as total intracellular reducing power. Vanadium is accumulated in mitochondria in particular when ‘‘decavanadate’’ is administered. These recent findings, that are now summarized, point out the decameric vanadate species contributions to in vivo and in vitro effects induced by vanadium in biological systems.